Pengaruh Struktur Kepemilikan dan Kinerja Lingkungan Terhadap Nilai Perusahaan - I Putu Adhi Saputra; Luh Putu Mahyuni (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe aim of this study is to investigate the effect of ownership structure and environmental performance on company value. The population of this study are companies listed on the Indonesia Stock Exchange and included in the PROPER assessment criteria for the 2014-2016 period. By using the purposive sampling method, a total of 21 companies were obtained. Path analysis was use to analyze the data. The study found that the ownership structure and environmental performance have a positive and significant effect on the value of the company. The study also found that ownership structure significantly influence environmental performance.